THE CHARACTERISTICS OF REMONSTRATION IN ARVIND ADIGA’S NOVELS - Fating, Madhura Pramod; Raut, Amol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The ideas and interactions of the people who live in a certain social, political, and geographic place are expressed in literature; the locals there embody political, social, religious, and moral beliefs. The divide between the ruling class and the working class, the rich and the impoverished, and the oppressive and the oppressed is enormous. Some members of the working class and needy who are eager to alter society stand in direct opposition to the restraints and conventions of repression. This entire procedure is a protest since they frequently fail but occasionally succeed. The novel's protagonist frequently challenges social norms and taboos, and his story is the focus of the entire work. A protagonist is forced to protest when he sees discrimination and humiliation based on caste, creed, religion, and status; this protest is also necessary to alter people's perspectives for the benefit of society. Arvind Adiga's work The White Tiger, which won the Booker Prize, made him renowned. Between the Assassinations (2008) is a collection of his short stories and two more novels. Arvind Adiga's books The White Tiger (2008) and Last Man in the Tower (2011) are specifically the subject of the study. He criticizes numerous inflexible, prevailing issues in all of his writings. The purpose of this study is to draw attention to the problems that have impacted a greater segment of the population.